Effect of Geometrical Properties on Localized Surface Plasmon Resonance of Gold Nanoparticles - Nguyen, Luong Lam; Trinh, Quoc Trung; Tu, Quang Bao; Nguyen, Van Quynh; Hoang, Thi Hong Cam (Communications in Physics, 2021)
This work reportson plasmonic effects (i.e light scattering and absorption properties) induced by two different gold nanoparticles (AuNPs)-shaped: spherical particle and triangular particle. The scattering cross-section and electric field profiles have been investigated by using theboundary element method (MNPBEM toolbox). Two configurations: the isolated AuNPand the coupledtwo-gold NPsystem have been considered to evaluate the localized surface plasmon resonance (LSPR) in eithersingle or coupled AuNPstructures. The effect of the surrounding medium on the scattering behavior of the NPs has also been examined. Then the dependence of “hotspot” intensity on the distance between two NPs has been recognized by mapping the electric field profile. The obtained results can be used as the guidelines for synthesizing AuNP structures to employ LSPR for sensing or other applications.